2005
DOI: 10.1074/jbc.m504616200
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Calmodulin-binding Transcription Factor from Rice (Oryza sativa L.)

Abstract: Calmodulin (CaM) regulates diverse cellular functions by modulating the activities of a variety of enzymes and proteins. However, direct modulation of transcription factors by CaM has been poorly understood. In this study, we isolated a putative transcription factor by screening a rice cDNA expression library by using CaM:horseradish peroxidase as a probe. This factor, which we have designated OsCBT (Oryza sativa CaM-binding transcription factor), has structural features similar to Arabidopsis AtSRs/AtCAMTAs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
128
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(133 citation statements)
references
References 48 publications
3
128
0
2
Order By: Relevance
“…CaM also regulates the transcriptional activities of transcription factors. CaM actually binds transcription factors and activates or inhibits their DNA-binding properties (13)(14)(15)(16)32). In this report, we isolated a CaM-binding NAC transcription factor (CBNAC) that can function as a transcriptional repressor.…”
Section: Cbnac Is a Cam-binding Transcription Repressor Protein-mentioning
confidence: 99%
See 3 more Smart Citations
“…CaM also regulates the transcriptional activities of transcription factors. CaM actually binds transcription factors and activates or inhibits their DNA-binding properties (13)(14)(15)(16)32). In this report, we isolated a CaM-binding NAC transcription factor (CBNAC) that can function as a transcriptional repressor.…”
Section: Cbnac Is a Cam-binding Transcription Repressor Protein-mentioning
confidence: 99%
“…Full-length CBNAC cDNA was obtained by PCR using a 5Ј primer containing a BamHI site and a 3Ј primer containing an SmaI site. The PCR product was inserted into the pUC::smGFP expression vector (32). Plasmids were introduced by polyethylene glycol-mediated transformation (33) into Arabidopsis protoplasts prepared from leaf tissues.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this study provided evidence that CaM is involved in regulating the activity of a defense-associated TF, it did not link the pathogen-induced Ca 2+ signature to transcription. Choi et al (2005) studied the function of the rice CAMTAs (Os-CBTs) in Arabidopsis protoplasts using synthetic promoters and found that Ca 2+ /CaM suppressed the CAMTA-mediated transcription activation. Constitutive activation of plant defense responses in camta3 mutants is temperature dependent (Du et al, 2009).…”
Section: The Role Of Cam Binding Tfs In Plant Immunitymentioning
confidence: 99%